The Role of Amygdala in Patients With Euthymic Bipolar Disorder During Resting State - Li, Gaizhi; Liu, Penghong; Andari, Elissar; Zhang, Aixia; Zhang, Kerang (Frontiers in Psychiatry, 2018)
The current study aimed to explore the functional changes of amygdala in patients with euthymic Bipolar Disorder (BD) using resting state fMRI (rs-fMRI). Twenty-one euthymic patients with bipolar disorder and twenty-eight healthy controls participated in this study, two of the euthymic patients with BD and three of the healthy controls were excluded due to excessive head motion. Patients with euthymia (38.79±12.03) show higher fALFF (fractional Amplitude of low-frequency fluctuation) value of amygdala (t = 2.076, P = 0.044) and lower functional connectivity between the amygdala and supplementary motor area (p<0.01, GRF corrected) than the healthy controls (33.10±8.21). However, euthymic patients did not show a differential activity in ReHo (Regional Homogeneity) and gray matter of amygdala region as compared to healthy controls. Thus, it is possible that despite the absence of clinical symptoms, amygdala activity during resting state remains altered in these euthymic patients with BD.